Upaya Meningkatkan Hasil Belajar PAI Materi Iman Kepada Malaikat Melalui Model Pembelajaran Snowball Throwing Bagi Siswa Kelas IV SDN Pucangan 02 Kartasura Semester II Tahun Pelajaran 2021/2022 - Nanik Alfiyah (Universitas Veteran Bangun Nusantara, 2022)
This study aims to improve the learning achievement of PAI subjects on faith in angels through snowball throwing lessons for fourth semester students of SD Negeri Pucangan 02, Kartasura District, Sukoharjo Regency in the 2021/2022 academic year. This research is a classroom action research. The research was conducted at SD Negeri Pucangan 02, Kartasura District, Sukoharjo Regency in the second semester of the 2021/2022 academic year for 3 (three) months. The research subjects were students of class V Semester II at SD Negeri Pucangan 02 Kartasura District, Sukoharjo Regency in the 2021/2022 academic year which consisted of 23 students. The research procedure in this action research basically refers to the research design used, namely: 1) planning; 2) implementation; 3) observation; and 4) reflection on the results of the action. This study concludes that Snowball Throwing Learning can improve student achievement in PAI subjects on faith in angels in grade IV semester II students of SD Negeri Pucangan 02, Kartasura District, Sukoharjo Regency in the 2021/2022 academic year. This is indicated by the increase in student learning outcomes from the initial condition to the end of the Cycle II action. In terms of the average value of learning outcomes, student learning achievement has increased from 68.82 in the initial condition, increased to 76.47 at the end of Cycle I learning action, and increased again to 87.65 at the end of Cycle II action. Judging from the level of mastery learning, the number of students who achieve mastery learning has increased in each cycle of actions taken, namely from 52.94% in the initial conditions to 76.47% at the end of the Cycle I action, and increased to 100% at the end of the Cycle II learning action. Keywords: learning achievement, PAI, Snowball Abstrak: Penelitian ini bertujuan untuk untuk meningkatkan prestasi belajar mata pelajaran PAI materi iman kepada malaikat melalui pembelajaran snowball throwing pada siswa kelas IV semester II SD Negeri Pucangan 02, Kecamatan Kartasura, Kabupaten Sukoharjo tahun pelajaran 2021/2022.Penelitian ini merupakan penelitian tindakan kelas. Penelitian dilakukan di SD Negeri Pucangan 02 Kecamatan Kartasura, Kabupaten Sukoharjo pada semester II tahun pelajaran 2021/2022 selama 3 (tiga) bulan. Subjek penelitian adalah siswa kelas V Semester II di SD Negeri Pucangan 02 Kecamatan Kartasura, Kabupaten Sukoharjo tahun pelajaran 2021/2022 yang terdiri dari 23 orang siswa. Prosedur penelitian dalam penelitian tindakan ini pada intinya mengacu pada desain penelitian yang digunakan, yaitu: 1) perencanaan; 2) pelaksanaan; 3) observasi; dan 4) refleksi hasil tindakan.Penelitian ini menyimpulkan bahwa Pembelajaran Snowball Throwing dapat meningkatkan prestasi belajar siswa mata pelajaran PAI materi iman kepada malaikat pada siswa kelas IV semester II SD Negeri Pucangan 02, Kecamatan Kartasura, Kabupaten Sukoharjo tahun pelajaran 2021/2022. Hal ini ditunjukkan dengan meningkatnya hasil belajar siswa dari kondisi awal hingga akhir tindakan Siklus II.Ditinjau dari nilai rata-rata hasil belajar, prestasi belajar siswa mengalami peningkatan dari sebesar 68.82 pada kondisi awal, meningkat menjadi 76.47 pada akhir tindakan pembelajaran Siklus I, dan meningkat lagi menjadi 87.65 pada akhir tindakan Siklus II. Ditinjau dari tingkat ketuntasan belajar, jumlah siswa yang mencapai ketuntasan belajar mengalami peningkatan pada setiap siklus tindakan yang dilakukan, yaitu dari 52,94% pada kondisi awal menjadi 76.47% pada akhir tindakan Siklus I, dan meningkat menjadi 100% pada akhir tindakan pembelajaran Siklus II. Kata-kata Kunci: prestasi belajar, PAI, Snowball